A Short Survey of the Working of the Five Year Plan From April 1951 to September 1953 - Planning Commission (Planning Commission Government of India, 1953)
This summary reviews the progress of India’s First Five-Year Plan during the early 1950s, highlighting achievements and challenges in agriculture, industry, infrastructure, social services, and land reforms. The Plan focused on stabilizing the post-independence economy, improving food security, generating employment, and laying the foundations for long-term development. Notable gains were recorded in agricultural production, irrigation expansion, industrial capacity utilization, and the extension of health and educational services. At the same time, shortcomings emerged in expenditure realization, cottage and small-scale industries, and the pace of land reform implementation. The report underscores the importance of public participation, cooperative farming, and local governance in advancing rural development. Overall, the assessment reflects a mixed but constructive beginning to India’s planned development, providing a foundation for subsequent planning efforts aimed at equitable and sustained economic growth.
Progress of the Plan
Government of India Planning Commission
Keywords: First FiveYear Plan; Economic Development; Agricultural Growth; Industrial Capacity; Infrastructure Development; Employment Generation; Land Reforms; Cooperative Farming; Social Services; Public Participation; Cottage Industries; Planning Commission